2012
DOI: 10.1371/journal.pone.0033118
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Aerosol Transmission of Pandemic and Seasonal H1N1 Influenza Viruses in the Ferret

Abstract: Person-to-person transmission of influenza viruses occurs by contact (direct and fomites) and non-contact (droplet and small particle aerosol) routes, but the quantitative dynamics and relative contributions of these routes are incompletely understood. The transmissibility of influenza strains estimated from secondary attack rates in closed human populations is confounded by large variations in population susceptibilities. An experimental method to phenotype strains for transmissibility in an animal model coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
73
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 50 publications
(77 reference statements)
5
73
0
Order By: Relevance
“…The detection of infectious influenza virus in respirable aerosols highlights the potential for a role of respirable aerosols in transmission events occurring during RDT experiments. Others have shown that influenza virus present in particles Ͻ15 m is responsible for transmission of virus between ferrets, although only viral RNA was detected in these studies (13,35). It is also plausible that aerosols play a role in transmission experiments in which animals are housed in direct contact; the contribution of close-range aerosol transmission cannot be ruled out in these scenarios (36).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The detection of infectious influenza virus in respirable aerosols highlights the potential for a role of respirable aerosols in transmission events occurring during RDT experiments. Others have shown that influenza virus present in particles Ͻ15 m is responsible for transmission of virus between ferrets, although only viral RNA was detected in these studies (13,35). It is also plausible that aerosols play a role in transmission experiments in which animals are housed in direct contact; the contribution of close-range aerosol transmission cannot be ruled out in these scenarios (36).…”
Section: Discussionmentioning
confidence: 82%
“…The majority of the aerosols measured in the current study during normal breathing were in the respirable size range, but when the volumes were compared, a greater difference between the two groups of infected animals was revealed at the submicrometer particle size range (Ͻ1 m), albeit with substantial variability. Others have measured the size distribution of aerosols in air exhausted from cages housing ferrets infected by influenza virus and have reported the greatest concentrations of particles in the submicrometer size range (13). Submicrometer aerosols may remain suspended in still air for 12 hours or more, increasing the opportunity for aerosols of this size to be inhaled (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, once contact is established, the animals typically remain in continuous exposure for the duration of the experiment. However, several studies have modulated this parameter, creating contact pairs for short periods of time during the acute phase of infection to better understand the temporal dynamics of virus transmission in the ferret model (49,70) or establishing contact at different times throughout the acute phase of infection to determine links between virus shedding in inoculated ferrets and virus transmissibility (71). Donor chains, where virus is serially transmitted or passaged from ferret to ferret, have also been employed to model the selective pressure that may occur by sustained transmission of viruses through a population (72)(73)(74).…”
Section: Transmission Experimental Designsmentioning
confidence: 99%
“…The distance between these paired cages is typically proximal (separated by only 3 mm to 10 cm) (38,77), depending on the construction of the cages and the experimental design, though transmission from inoculated to susceptible ferrets has been reported at distances up to 5 feet (63). Furthermore, airflow in transmission caging can vary between laboratories, with examples of directional flow from the inoculated ferret to the contact ferret (70,75,77) or top-to-bottom (31,38), bottom-to-top (73), front-to-back (76), or unspecified (14) directionality. Modulation of temperature and relative humidity, the study of which was previously limited to the guinea pig transmission model (78,79), has also recently been shown to affect virus transmissibility in ferrets (80).…”
Section: Transmission Experimental Designsmentioning
confidence: 99%